Purposefulness of Physical Education Teachers as a Determinant of Their Pupils’ Objective Position in Physical Education Activities in Postmodern Society - Kardelienė, Laimutė (Pedagogika, 2016)
The peculiarities of youth way of living show that great deal of attention should be paid to the rapid change of interests in physical education activities during their leisure time as well as a school subject. Physical education teachers, as professionals, are deliberately trying to create a pleasant study atmosphere. Furthermore, the pupils show appreciation for the teacher’s ability to sustain a positive outlook towards physical education activities. Professional purposefulness of a teacher must be assessed in order to consolidate a personal education approach. Therefore, a research question is formulated: which type of professional purposefulness is dominant amongst physical education teachers? Research object – a subjective self-evaluation of physical education teachers’ purposefulness. Research aim – to evaluate physical education teachers’ professional purposefulness as means of increasing pupils’ positive outlook towards physical education activities. Methods. An independent sample was constructed. A scale of 21 statements was used to evaluate teachers’ educational purposefulness and professional competences that describe it. Conclusion. A comparative analysis of data, revealing physical education teachers’ professional purposefulness, and attitude towards physical education classes has shown that teachers who practice goal-oriented purposefulness, compared to those of situational purposefulness, tend to be more creative during classes and more concerned with the importance of physical education in the curriculum. Connections of research variables show that goal-oriented purposefulness teachers are more physically active during their leisure time, are more optimistic about their current life stage and are more successful at creating an educational environment during their classes.